Genome-Wide Identification of the Remorin Gene Family in Poplar and Their Responses to Abiotic Stresses - Zihui Li; Hang Wang; Chuanqi Li; Huimin Liu; Jie Luo (Life)
The Remorin (REM) gene family is a plant-specific, oligomeric, filamentous family protein located on the cell membrane, which is important for plant growth and stress responses. In this study, a total of 22 PtREMs were identified in the genome of Populus trichocarpa. Subcellular localization analysis showed that they were predictively distributed in the cell membrane and nucleus. Only five PtREMs members contain both Remorin_C- and Remorin_N-conserved domains, and most of them only contain the Remorin_C domain. A total of 20 gene duplication pairs were found, all of which belonged to fragment duplication. Molecular evolutionary analysis showed the PtREMs have undergone purified selection. Lots of cis-acting elements assigned into categories of plant growth and development, stress response, hormone response and light response were detected in the promoters of PtREMs. PtREMs showed distinct gene expression patterns in response to diverse stress conditions where the mRNA levels of PtREM4.1, PtREM4.2 and PtREM6.11 were induced in most cases. A co-expression network centered by PtREMs was constructed to uncover the possible functions of PtREMs in protein modification, microtube-based movement and hormone signaling. The obtained results shed new light on understanding the roles of PtREMs in coping with environmental stresses in poplar species.